Career guidance in Quebec, Canada - Dupont, Pierrette (1999)
First, the guidance counselor profession in the province of Quebec will be described: the professional association to which it belongs, the required instruction, the counselors' tasks and the institutions for which they work. There follows the description of the main current tendencies in career guidance development in this French-speaking area of Canada with about 7.2 million inhabitants, approximately one fourth of the total country population. Finally, a brief description of the Center for Research on Education and Labor of the University of Shebrooke as well as of some instruments that one of the teams is constructing will be provided.